Received 3 March 2026; Received in revised form 11 March 2026 year; Accepted 28 March 2026 Available online 10 April 2026 / © 2026 The Authors. Published by Jurnal Teknik Industri Terintegrasi Universitas Pahlawan Tuanku Tambusai. This is an open access article under the CC BY-SA license (https://creativecommons.org/licenses/by-sa/4.0) - Nidak, Ahmad Choirun; Fatmawati, Laily Endah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The rapid development of high-rise buildings in Indonesia demands a stable and safe planning structure, especially for the foundation as an element that transfers the load to the subgrade. The Husada Prima Hospital Service Development Building uses a 15 m deep bored pile foundation, chosen because it can minimize vibration and disturbance in densely populated areas. Based on N-SPT data, the soil is dominated by fine to medium graded sand with loose to dense density, so the pile has not reached the hard soil layer. To improve performance, a fullplatee was added to the pile cap to reduce stress concentration. The bearing capacity and settlement analysis were performed using the Aoki–De Alencar method, then validated through numerical modeling with PLAXIS to obtain a more realistic picture of soil–structure interaction. The results of this study are expected to provide a comprehensive evaluation of foundation performance and ensure the safety and stability of the structure.